Leaf metabolome in arbuscular mycorrhizal symbiosis. (August 2015) - Schweiger, Rabea; Müller, Caroline
Graphical abstract: Highlights: Arbuscular mycorrhizal fungi in plant roots systemically affect leaf metabolites. Targeted analyses reveal effects on certain leaf primary and secondary metabolites. Omics approaches are needed to gain comprehensive insights into leaf responses. Many metabolite classes of various plant species respond specifically. Mycorrhiza-mediated metabolic changes affect interactions with the environment. Abstract : Most land plants are associated with arbuscular mycorrhizal fungi, which colonise the plant roots and facilitate the uptake of water and nutrients. In turn, the fungi receive plant carbohydrates. Although the fungus is morphologically restricted to the roots, the exchange of substances and involvement of phytohormone signalling has consequences on systemic shoot tissues. Recent research provides growing insight in the species-specificity of leaf metabolic responses to arbuscular mycorrhiza, revealing that various metabolites can be affected. Such mycorrhiza-mediated changes in the chemical composition of leaf tissues can confer phytoprotection against different abiotic stresses. Moreover, they have consequences on numerous biotic interactions. In this review we highlight such findings and point out fields where more research is required.